François Mittérand : 1916 - 1996 - Joffrin, Laurent; Daniel, Jean; Schneider, Robert (Paris: Le Nouvel Observateur, 1996)
"Laurent Joffrin; Jean Daniel; Robert Schneider... et al. Speciaal nummer van Le Nouvel Observateur (1996) 1627"